The Incorporation of Character-Building Values in Digital Learning Materials for SMP Students - Hartanto, Muhammad Dimas; Agustina, Imas Wahyu; Mayuni, Ilza (STAIRS: English Language Education Journal, 2022)
This study investigated the incorporation of Profil Pelajar Pancasila in digital learning materials for Junior High School students. This study applied the content analysis method, the data of which were learning materials provided on Myenglishstep.com for every level of Junior High School. The data were analyzed by comparing them with 19 indicators which were derived from six dimensions of Profil Pelajar Pancasila. The results showed that 230 data fulfilled all 19 indicators and were incorporated into various forms of learning materials. The highest occurrences (80 data) were found in the fifth dimension which is to think critically (Dimensi Berfikir Kritis) while the lowest (10 data) occurred in global diversity (Dimensi Kebhinekaan Global). In addition, the values of Profil Pelajar Pancasila were mostly incorporated through task instructions (98 data), followed by live worksheets (64 data), videos (34 data), and audios (13 data). This result indicates that the digital learning materials available on the website of Myenglishstep.com are aligned with the character-building values proposed in Profil Pelajar Pancasila, thus, they become worth trying to support English language learning at the Junior High levels in Indonesia.